1996
DOI: 10.1159/000169042
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Systemic Hemodynamics in Falciparum Malaria

Abstract: Renal and systemic hemodynamics, plasma arginine vasopressin, plasma renin activity, plasma norepinephrine, blood volume and water loading test were studied in 10 patients with falciparum malaria without renal failure. Six patients responded to water load normally, while 4 patients had a decreased response to water load. The patients with a normal water load response had normal renal and systemic hemodynamics and a normal hormonal profile. The patients with a decreased response to water load had hyponatremia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 22 publications
(33 reference statements)
1
32
0
Order By: Relevance
“…The first generation of post capillary venules range in size from 10 μm to 30 μm and the second generation from 40 μm to 200 μm, whereas the diameter of the spherical PRBC is not larger than 4.4 μm. There is, therefore, plenty of room for circulation to continue, especially with vasodilatation, for which there is some evidence of occurrence in malaria infections [23-25]. PRBC are more rigid and less deformable than uninfected RBC (although these are also less deformable than normal RBC) [26,27] and thus increase blood viscosity [28-30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first generation of post capillary venules range in size from 10 μm to 30 μm and the second generation from 40 μm to 200 μm, whereas the diameter of the spherical PRBC is not larger than 4.4 μm. There is, therefore, plenty of room for circulation to continue, especially with vasodilatation, for which there is some evidence of occurrence in malaria infections [23-25]. PRBC are more rigid and less deformable than uninfected RBC (although these are also less deformable than normal RBC) [26,27] and thus increase blood viscosity [28-30].…”
Section: Introductionmentioning
confidence: 99%
“…Histology, however, indicates that even in severe malaria not all venules are obstructed. Vasodilatation, which has been observed by some investigators in malaria patients [23,43], is known not to affect venules directly, but feeding arteries and arterioles. Flow in capillaries in the healthy host is typically intermittent and not all capillaries necessarily allow blood flow all the time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] This is similar to the findings in malaria. [10] At the clinical level, there may be subclinical hypotension or clinical hypotension when the disease is severe. [11] A decreased response to fluid load has been observed.…”
Section: Discussionmentioning
confidence: 99%
“…Small series have confirmed that some adult patients with severe malaria are hypovolaemic, or at least have a reduced effective circulating volume [7], [8]. This hypovolaemia has the potential to exacerbate renal failure and lactic acidosis, two of the most significant contributors to mortality in severe malaria [9].…”
Section: Introductionmentioning
confidence: 98%